1990
DOI: 10.1002/tl.37219904310
|View full text |Cite
|
Sign up to set email alerts
|

Students do rate different academic fields differently

Abstract: Research on the variables that may bias student ratings has largely found these variables to have little influence. One exception concerns academic fields. Institutions and individuals should decide how they will take academic‐field differences into consideration when they interpret student ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 3 publications
7
62
0
5
Order By: Relevance
“…Classroom processes often differÑpsychology tutorial classes are most often based on discussions amongst the students and with the instructor, whereas physical sciences tutorial classes are most often based on solving worksheet questions. How psychology students perceive their instructors may also differ, given findings indicating that students rate social sciences and humanities instructors more favorably than mathematics and science instructors (Cashin, 1990) and that certain university instructor qualities (such as pragmatism) is related to student evaluations in natural sciences but not in humanities nor social sciences (Sherman & Blackburn, 1975). Thus, we examine students in a university psychology course to test whether the results from Study 1 regarding ideal instructor personality generalizes to a social sciences subject area.…”
Section: Studymentioning
confidence: 99%
“…Classroom processes often differÑpsychology tutorial classes are most often based on discussions amongst the students and with the instructor, whereas physical sciences tutorial classes are most often based on solving worksheet questions. How psychology students perceive their instructors may also differ, given findings indicating that students rate social sciences and humanities instructors more favorably than mathematics and science instructors (Cashin, 1990) and that certain university instructor qualities (such as pragmatism) is related to student evaluations in natural sciences but not in humanities nor social sciences (Sherman & Blackburn, 1975). Thus, we examine students in a university psychology course to test whether the results from Study 1 regarding ideal instructor personality generalizes to a social sciences subject area.…”
Section: Studymentioning
confidence: 99%
“…The large survey by Cashin (1990) found that the disciplinary differences in ratings explained only a modest percentage of the variance, but of sufficient magnitude that the effect could not be ignored. As pointed out by Kwan (1999, p. 184) and Marsh (1987, p. 309) the percentage of variance shows the strength of the relationship between variables and the explanatory power.…”
mentioning
confidence: 98%
“…Feldman (1978) reviewed 11 studies which compared ratings across disciplines and found that the humanities and arts tended to be rated higher than sciences, engineering and business administration. Cashin (1990) analysed large data sets from two widely used course evaluation instruments in the US to find that ratings tended to be higher in the arts and humanities than in science, engineering and business. Barnes and Patterson (1988) also produced closely related findings.…”
mentioning
confidence: 99%
“…Whether subject itself has an effect on evaluation or not has also been a focus of studies. It has been found that Humanities and Art type subjects receive higher ratings than Mathematics-type courses, as students tend to feel incompetent in quantitative skills (Braskamp & Ory, 1994;Cashin, 1990;Neumann, 2000). Student-level factors include student biases, reasons of taking the course, the effort student expend in the subject, age, ethnicity, gender, and students' grade expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Student-level factors include student biases, reasons of taking the course, the effort student expend in the subject, age, ethnicity, gender, and students' grade expectations. Studies on gender have yielded inconclusive results, as some support potential biases, while others indicate that gender has no effect on evaluation (Basow, 2000;Cashin, 1990;Feldman, 1993;Wolfer & Johnson, 2003). However, Mason, Steagall and Fabritus (1995) claim that females are more likely to give positive ratings of teacher effectiveness.…”
Section: Introductionmentioning
confidence: 99%